FAKTOR LINGKUNGAN KONSUMEN, KELOMPOK ACUAN DAN E-WOM DALAM EKOSISTEM MEDIA SOSIAL : STUDI KASUS VIRAL MARKETING ALDIS BURGER - Fajrina Fatil Minati; Yuliani Setia Ningrum; silvy dewi anggraini; Aldi Saifulloh; irvaia miftakhul jannah; m. naizil ma'wqa; destania shezylia rossi putri (Mount Hope Management International Journal, 2026)
The development of social media has encouraged the emergence of various digital marketing strategies, one of which is viral marketing. The phenomenon of Aldis Burger promoted by Aldi Taher is interesting to study because of its success in attracting public attention through social media and the personal branding of public figures. This study aims to analyze consumer behavior in responding to Aldis Burger's viral marketing strategy based on cultural, demographic, economic, social, family and reference group factors, as well as technology and electronic word of mouth (e-WOM). The study uses a qualitative descriptive approach with the ADD case study method. The data source was obtained from an Instagram post @Bisnishack Official entitled "Don't Copy Aldi Taher's Viral Marketing", supported by various relevant literature and previous research. The analysis technique was carried out through content analysis of the post's content and linked to consumer behavior theory. The results of the study indicate that viral marketing can increase consumer attention and curiosity about the product. In addition, digital culture, demographic characteristics of the younger generation, economic considerations, the influence of family and reference groups, and the dissemination of information through social media and e-WOM also influence consumer interest and purchasing decisions. These findings suggest that the success of a digital marketing strategy is the result of the interaction between viral marketing and consumer behavioral factors in the digital environment.